Heavy Metal Accumulation in Vegetables Grown in Rock Soils of Kilembe Copper Mine, Kasese, Western Uganda - Masereka, Jockus; Byamugisha, Denis; Adaku, Christopher (Asian Journal of Applied Chemistry Research, 2022)
Aim: Active mining in Kilembe copper mine, Kasese district, Uganda ended about four decades ago. However, various health problems are believed to be from the effect of mining activities that took place in the area. In this study therefore, we quantified the concentration of trace metals: chromium (Cr), cadmium (Cd), zinc (Zn), iron (Fe), lead (Pb), arsenic (As) and copper (Cu) in cabbages and tomatoes grown in Kilembe mining area and assessed the health risks from consumption of the vegetables after 40 days and 120 days of growth. Study Design: This study employed quantitative research design. Place and Duration of Study: The experiments were done at Department of Chemistry, Mbarara University of Science and Technology, Uganda from 2018 to 2019. Methodology: The vegetables were planted, and their roots, leaves, fruits and stems were sampled after 40 days and 120 days. Elemental analysis was performed using atomic absorption spectrophotometry. The estimated daily intake (EDI), target harzard quotient (THQ) and cancer risks were calculated to explore health risks that could arise from consumption of the vegetables. Results: The levels of Fe, Cu, Zn and Cr did not exceed WHO/FAO permissible limits. The EDI of Fe (294.678 × 10-4 mg/kg/day) was the highest while the lowest was 0.052 × 10-4 mg/kg/day for Cr The THQ ranged from 0.000004 to 1.3134. Cancer risk values ranged from 0.126 × 10-4 to 28650 × 10-4. Conclusion: There are discernable non-carcinogenic health risks (THQ >1) and cancer risks associated with consumption of cabbages and tomatoes by the local inhabitants. The risks are escalated in children who consume both vegetables after 40 days of growth. Arsenic and Cd poses the highest carcinogenic health risk while Pb poses the highest non-carcinogenic health risk. Consumption of the vegetables after 120 days of growth poses lower health risks.
Keywords: Trace metals; Target hazard quotient; Hazard index; Estimated daily intake; Carcinogenic risk